Improving Grade VIII Students™ Vocabulary Achievement By Using Personal Vocabulary Notes In SMP SANTA MARIA MEDAN - Panjaitan, Nova Ivanna; Ginting, Elia Masa (TRANSFORM: Journal of English Language Teaching and Learning, 2012)
This study attempts to  improve students™ vocabulary achievement by using Personal Vocabulary Notes. This research was conducted by using classroom action research. The subject of this study was VIII-B class SMP Santa Maria Medan which consisted of 46 students. The research was conducted in two cycles and each cycle consisted of three meetings. The result showed that the improvement of the students™ scores from the first test in orientation test to the third test in cycle-II test. In the first test in orientation test, the mean was 46.95, in the second test in cycle-I test, the mean was 64.86, and the third test in cycle-II test, it was improved to be 80.45. Based on the diary notes, observation sheet, and questionnaire, it was found that the teaching learning activities ran well. Students were active and enthusiastic during the teaching learning process in the second cycle than the first one. The result of the researcher showed that the use of personal vocabulary notes significantly improved students™ vocabulary.   Keywords: Vocabulary, Action Research, Personal Vocabulary Notes